Duo para Oboé e Fagote de Heitor Villa-Lobos: um estudo analítico para uma proposta interpretativa para o oboé - Ravi Shankar Viana Domingues (2014)
This dissertation is an analytical study of Villa-Lobos' Duet for oboe and bassoon (1957) which approaches the work's technical challenges and the composition processes used by the composer, in order to offer suggestions for interpretation of the oboe part. The Duet, given its technical complexity and the composer's masterful writing for both instruments, as well as for being one of very few works originally written for oboe and bassoon, is a relevant work in the Brazilian chamber music repertoire for this formation. In order to better understand Villa-Lobos' musical production, we contextualized his compositional periods using historical references, focusing on his latest compositional period and the whole of his chamber music writing. We present here the parameters upon which we elaborated the interpretative suggestions for oboists regarding breathing, articulation, phrasing, fingerings and dynamics. Individual practice and study of the work as well as rehearsals with bassoonist Catherine Carignan determined the suggestions given for each of the three movements, as found in the performance edition. In this context, the main purpose of this paper was the development of a performance edition for the oboe part seeking to assist the interpretation of the work through the vision of an oboist about some of the most relevant aspects for the performance.